Intensive chemotherapy with blood progenitor transplantation for primary resistant multiple myeloma - Dimopoulos, M.A.; Hester, J.; Huei, Y.; Champlin, R.; Alexanian, R. (British Journal of Haematology, 1994)
This study assessed the feasibility and effect of blood progenitors as the only source of haemopoietic support for myeloablative therapy for patients with primary resistant multiple myeloma and markedly infiltrated bone marrow. 17 patients with advanced, primary resistant myeloma received a priming regimen of cyclophosphamide (3 g/m2) and etoposide (900 mg/m2) with GM-CSF. During haematological recovery, at least 2 x 106 CD34+ mononuclear cells/ kg were collected from each patient with 4-12 leukaphereses. High-dose chemotherapy was then given which consisted of thiotepa (750 mg/m2), busulfan (10 mg/kg) and cyclophosphamide (120 mg/kg) followed by reinfusion of the blood progenitors. Haemopoietic reconstitution was rapid with recovery of granulocytes to >1.0 x 109/l after a median of 10 d and of platelets to 50 x 109/l after a median of 29 d. The myeloma responded in 10/17 patients for a projected median duration of at least 12 months. Survival was prolonged significantly in comparison with the outcome of control patients who did not receive intensive treatment. Blood progenitors, assessed from the number of CD34+ cells, produced early haemopoietic recovery after myeloablative therapy that induced sustained control of advanced and resistant multiple myeloma.
Keywords: Intensive chemotherapy; Primary resistant multiple myeloma; Stem cell transplantation